Extension and advisory services: The African renaissance - Zwane, E. M.; Davis, Kristin E. (Academy of Science of South Africa, 2017)
This paper highlights the establishment of development organisations on the African continent and beyond, namely the New Partnership for Africa's Development's Comprehensive African Agricultural Development Programme (CAADP), the African Forum for Agricultural Advisory Services (AFAAS), and Southern Africa Regional Forum for Agricultural Advisory Services (SARFAAS), country forums (CF), and the Global Forum for Rural Advisory Services (GFRAS). These organisations can be considered as a source of renaissance in agricultural advisory services. They have facilitated the development of structures that advocate for extension and advisory services. These organisations have brought focus, and initiated debate on the concept of extension. The importance of such services is promoted as a means of assisting marginalised farmers and encouraging countries to adopt "pro-poor" approaches to farmer development. A literature review and expert opinion for analysis is provided to illustrate the findings, indicating different understandings of the concept of extension, and that extension actors are organised in sub-regional networks and countries as a link to GFRAS, AFAAS, and the New Partnership for Africa's Development (NEPAD), sub-program CAADP.